2009
DOI: 10.1002/adma.200802686
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a High‐Brightness Blue‐Light‐Emitting Diode Using a ZnO‐Nanowire Array Grown on p‐GaN Thin Film

Abstract: Bright n‐ZnO nanowire/p‐GaN film hybrid heterojunction light‐emitting‐diode (LED) devices are fabricated by directly growing n‐type ZnO‐nanowire arrays on p‐GaN wafers. UV–blue electroluminescence emission was observed from the heterojunction diodes, and the heterojunction LED device exhibited a high sensitivity in responding to UV irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
213
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 446 publications
(221 citation statements)
references
References 25 publications
3
213
2
3
Order By: Relevance
“…Whereas the redshifted violet emission band centered at about 430 nm was ascribed to the transitions from the conduction band or shallow donors to deep Mg acceptor levels in the p-GaN thin film substrate [372,377,380]. The blue emission at around 460 nm was assigned to the radiative interfacial recombination of the electrons from n-ZnO and holes from p-GaN [380][381][382]. The interface states generally act as nonradiative centers that annihilate free electrons and holes.…”
Section: Inorganic Heterojunction Ledsmentioning
confidence: 99%
“…Whereas the redshifted violet emission band centered at about 430 nm was ascribed to the transitions from the conduction band or shallow donors to deep Mg acceptor levels in the p-GaN thin film substrate [372,377,380]. The blue emission at around 460 nm was assigned to the radiative interfacial recombination of the electrons from n-ZnO and holes from p-GaN [380][381][382]. The interface states generally act as nonradiative centers that annihilate free electrons and holes.…”
Section: Inorganic Heterojunction Ledsmentioning
confidence: 99%
“…The round-shaped spot is originated from the whole disk-shaped ZnO nanowires layer. Most previous works exhibited a strong EL emission from forward bias beyond 10 V at higher wavelength [148][149][150][151][152]. Another study showed different EL behavior from other nZnO/p-GaN heterojunctions where the EL generated only from either the n-ZnO or p-GaN side [143].…”
Section: Hybrid / Heterostructuresmentioning
confidence: 93%
“…[17][18][19]. It has large exciton binding energy (60mV) and hexagonal shape, and is significantly applied in optics, electronics, sensors and actuators [20,21]. Based on morphological structure and the organization of ZnO, its properties and applications can be determined [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%